Estudo de viabilidade econômica da produção de pré-moldados de gesso e cinzas do carvão utilizado em usina termelétrica. - Nunes, Daniel Carlos (2017)
A localization model was developed and simulated in a spreadsheet for a pre-cast production process made by coaxial pressing, composed of a mixture of gypsum and coal ash used as fuel in a thermoelectric plant. The encapsulation of coal ash with a high sulfur content has been recommended to attenuate environmental liabilities and its use as an input of pre-cast gypsum based presents itself as an environmental solution of this residue and reduces the cost of material for civil construction. However, the geographical points where this waste is produced requires scholars to develop efficient logistic strategies, such as a model for optimized conditions, so that transport costs do not negate the high availability of these wastes to the areas located in Their environments. Preliminarily, experimental conditions were studied for the definition of proportions of components in precast. Next, a localization model was elaborated based on the geographic distances of the production points of the inputs, on the transportation costs of these materials and on the use of the mass / load center definition methodology. The routes of the means of transport were traced with the help of resources available on the Internet, allowing the creation of physical geographic models (maps). The mathematical localization model was simulated using the Solver tool from the Excel spreadsheet of Microfoft®. The installation point chosen for a company of gypsum and coal ash precast is at coordinates x = 0 and y = 589, in the city of Araripina (PE). The production of pre-cast with gypsum and charcoal gray, in addition to filling environmentally friendly solutions, contributes to increase the supply of new gypsum-based products.